1989
DOI: 10.1007/bf01865515
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of SIN-1 in acute left heart failure

Abstract: To assess the hemodynamic effects of SIN-1, the active metabolite of the venodilator molsidomine, after acute as well as chronic intravenous administration, ten patients with exacerbation of chronic heart failure were studied. After a mean bolus dose of 2 mg of SIN-1, mean right atrial pressure (MRAP), mean pulmonary artery pressure (MPAP), and pulmonary capillary wedge pressure (PCAP) decreased significantly up to the 60th minute; pulmonary vascular resistance (PVR) decreased significantly up to the 30th minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Haemodynamic effects identical to those demonstrated in the present study have been found with comparable dosage ferms of molsidomine and SIN-l, its major metabolite [22][23][24]. The present study, therefore, using different methods, has confirmed the sydnonimines as being substances which act predominantly on preload [22][23][24].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Haemodynamic effects identical to those demonstrated in the present study have been found with comparable dosage ferms of molsidomine and SIN-l, its major metabolite [22][23][24]. The present study, therefore, using different methods, has confirmed the sydnonimines as being substances which act predominantly on preload [22][23][24].…”
Section: Discussionsupporting
confidence: 74%
“…The present study, therefore, using different methods, has confirmed the sydnonimines as being substances which act predominantly on preload [22][23][24]. Nevertheless, there have been some reports [22][23][24][25] of decreases in total vascular resistance and, consequently, in after-load, as could also be seen from the tendency for such decreases to occur in the present study, and which was paralleled by increases in cardiac output taking place exclusively at the same points in time (Table 1). Consequently, since this points to a possibly dose dependent influence of molsidomine on all types of vascular resistance, administration of an even higher dose in sustained-release form would seem justified for effective treatment of chronic congestive heart failure, this should also affect left ventricular afterload, i.e.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations